Recent Texts on the Methods of Economic Statistics - Crum, W. L.; Chaddock, Robert Emmet; Day, Edmund E.; Secrist, Horace; King, Willford I. (Quarterly Journal of Economics, 1926)
Journal Article Recent Texts on the Methods of Economic Statistics Get access W. L. Crum W. L. Crum Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 40, Issue 3, May 1926, Pages 530–546, https://doi.org/10.2307/1885176 Published: 01 May 1926